An approach to analyzing synthesis, structure and properties of bismuth titanate ceramics - Lazarevic, Z. (2005)
The family of bismuth titanate, Bi(4)Ti(3)O(12) (BIT) layered-structured ferroelectrics materials is attractive from the viewpoint of such as their application as electronic materials dielectrics, piezoelectrics and pyroelectrics, because they are characterized by good stability of piezoelectric properties, a high Curie temperature and a good resistance vs temperature. Bismuth titanate (Bi(4)Ti(3)O(12)) powders can be prepared using different methods, depending if the creation will be film coating or ceramics. The structure and properties of bismuth titanate materials show a significance dependence on the applied synthesis method. In this review paper, we made an attempt to give an approach to analyszing the structure, synthesis methods and properties of bismuth titanate ferroelectrics materials.